Decreased Anti-Inflammatory Responses to Vitamin D in Neonatal Neutrophils - Daniel Hirsch; Faith E. Archer; Meera Joshi-Kale; Anna M. Vetrano; Barry Weinberger (Mediators of Inflammation)
Neutrophil activity is prolonged in newborns, suggesting decreased exposure and/or responses to immunosuppressive modulators, such as 1,25-hydroxyvitamin D3 (1,25-vit D3). We hypothesized that 1,25-vit D3 suppresses neutrophil activation and that this response is impaired in newborns. Consistent with this, 1,25-vit D3 decreased LPS-induced expression of macrophage inflammatory protein-1β and VEGF in adult, but not neonatal, neutrophils. Expression of vitamin D receptor (VDR) and 25-hydroxyvitamin D3-1α-hydroxylase was reduced in neonatal, relative to adult neutrophils. Moreover, 1,25-vit D3 induced VDR gene expression in activated adult, but not neonatal, neutrophils. 1,25-vit D3 also suppressed expression of cyclooxygenase-2 and induced expression of 5-lipoxygenase in LPS-exposed adult neutrophils, while neonatal cells were not affected. 1,25-vit D3 had no effect on respiratory burst in either adult or neonatal cells. Anti-inflammatory activity of vitamin D is impaired in neonatal neutrophils, and this may be due to decreased expression of VDR and 1α-hydroxylase. Insensitivity to 1,25-vit D3 may contribute to chronic inflammation in neonates.